Microbial co-infection of COVID-19 and therapeutic implications: literature review - Wani Devita Gunardi; Kris Herawan Timotius (Journal of Clinical Microbiology and Infectious Diseases, 2022)
Background: Attention to Covid-19 is shedding the role of co-infected microbial, bacteria, fungi, and non Covid-19 viruses. The presence and role of co-infected microbial is not fully understood. This review aims to find information about Covid-19 co-infected microbial, and to relate the findings with therapeutic implementation of Covid-19. Method: Relevant articles were searched from PubMed and then screened. Fifty articles were reviewed to answer the objectives. Result: Covid-19 infection involves co-infection of bacteria, yeast, fungi and viruses. The composition of the co-infected microbiome depends on the phase of the covid-19 infection, comorbid diseases, such as diabetes, and aging. This co-infection is associated with the phase and level of severity of Covid-19 infection. Conclusion: Analysis of possibility of co-infection is strongly needed in all phases of Covid-19 and has therapeutic implications for Covid-19.